2014
DOI: 10.4312/dp.41.14
|View full text |Cite
|
Sign up to set email alerts
|

A hoard of astragals discovered in the Copper Age settlement at Iepureşti, Giurgiu County, Romania

Abstract: This article presents the discovery of 25 abraded and perforated ovicaprid astragals in a burned house at the Gumelnita Copper Age settlement at Iepuresti in Southern Romania. They were analysed in terms of their processing, of the taphonomic processes that affected them (burning), and of their spatial distribution. These astragals were also analysed in the wider context of more or less similar discoveries made mainly south and east of the Carpathian Mountains, in Romania, but also south of the Danube, in Bulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…They were also identified in the Precucuteni culture, at Ghigoeş tiTrudeş ti (Marinescu-Bîlcu, 1974), Isaiia (Ursulescu et al, 2004), Târpeş ti (Marinescu-Bîlcu, 1974) and Târgu Frumos (Vornicu, 2014). These pieces are present in the middle Chalcolithic, especially for the Gumelnit¸a culture, at Hârş ova-tell, Borduş ani-Popin a, Vit aneş ti, M ariut¸a-tell (M arg arit et al, 2014b), Cuneş ti (M arg arit et al, 2013), Gumelnit¸a (Dumitrescu, 1966),Însur at¸ei-Popin a I (Pandrea et al, 2002), N avodari-Insula la Ostrov (Marinescu-Bîlcu et al, 2001, and Iepureş ti (Kog alniceanu et al, 2014). An abraded astragalus deposit was discovered in a burned dwelling from the Cucuteni settlement of Poduri-Dealul Ghindaru (Bejenaru et al, 2010).…”
Section: Abraded Astragalusmentioning
confidence: 97%
“…They were also identified in the Precucuteni culture, at Ghigoeş tiTrudeş ti (Marinescu-Bîlcu, 1974), Isaiia (Ursulescu et al, 2004), Târpeş ti (Marinescu-Bîlcu, 1974) and Târgu Frumos (Vornicu, 2014). These pieces are present in the middle Chalcolithic, especially for the Gumelnit¸a culture, at Hârş ova-tell, Borduş ani-Popin a, Vit aneş ti, M ariut¸a-tell (M arg arit et al, 2014b), Cuneş ti (M arg arit et al, 2013), Gumelnit¸a (Dumitrescu, 1966),Însur at¸ei-Popin a I (Pandrea et al, 2002), N avodari-Insula la Ostrov (Marinescu-Bîlcu et al, 2001, and Iepureş ti (Kog alniceanu et al, 2014). An abraded astragalus deposit was discovered in a burned dwelling from the Cucuteni settlement of Poduri-Dealul Ghindaru (Bejenaru et al, 2010).…”
Section: Abraded Astragalusmentioning
confidence: 97%
“…Modificirani astragali, vjerojatno različitih namjena, sreću se u brojnim prapovijesnim kulturama u Europi; između ostalog, u kasno neolitičkoj vinčanskoj kulturi (Vitezović 2007), kao i u eneolitičkim kulturama u Rumunjskoj (e.g., Kogǎlniceanu et al 2014) Several modified astragals with traces of use were found, from red deer, sheep and pig ( Fig. 4).…”
Section: Kulturni Kompleks Bubanj-sălcuţa-krivodolunclassified
“…Modified astragals, probably od different functions, can be encountered among the numerous prehistoric cultures in Europe; among others, in the Late Neolithic Vinča culture (Vitezović 2007), among Eneolithic cultures in Romania (e.g., Kogǎlniceanu et al 2014) and Bulgaria (e.g., Zidarov 2005), in the Bronze Age in Hungary (Meier 2013), and so on. (Tasić 1995: 172-173).…”
Section: Kulturni Kompleks Bubanj-sălcuţa-krivodolmentioning
confidence: 99%
“…4 Monah 1997; Bailey 2005; Ștefan 2006; Ștefan 2013. 5, Schuster et al 2010 Schuster et al 2012;Kogălniceanu et al 2014a. 6 Kogălniceanu et al 2014b Morintz și Kogălniceanu 2012.…”
unclassified